Aspergillus-Related Lung Disease - Alia Al-Alawi; C Frank Ryan; Julia D Flint; Nestor L Müller (Canadian Respiratory Journal)
Aspergillus is a ubiquitous dimorphic fungus that causes a variety of human diseases ranging in severity from trivial to life-threatening, depending on the host response. An intact host defence is important to prevent disease, but individuals with pre-existing structural lung disease, atopy, occupational exposure or impaired immunity are susceptible. Three distinctive patterns of aspergillus-related lung disease are recognized: saprophytic infestation of airways, cavities and necrotic tissue; allergic disease including extrinsic allergic alveolitis, asthma, allergic bronchopulmonary aspergillosis, bronchocentric granulomatosis and chronic eosinophilic pneumonia; and airway and tissue invasive disease -- pseudomembranous tracheobronchitis, acute bronchopneumonia, angioinvasive aspergillosis, chronic necrotizing aspergillosis and invasive pleural disease. A broad knowledge of these clinical presentations and a high index of suspicion are required to ensure timely diagnosis and treatment of the potentially lethal manifestations of aspergillus-related pulmonary disease. In the present report, the clinical, radiographic and pathological aspects of the various aspergillus-related lung diseases are briefly reviewed.